Small ubiquitin-like modifiers inhibitors lower blood pressure via ERK5/KLF2-dependent upregulation of the eNOS/NO pathway - Tang Nannan; Li Jiatong; Wang Zhuo; Zuo Jinlu; Zhang Zifeng; Huang Di; Han Yannan; Chen Yuqing; Sun Yilin; Li Xiang; Mu Ruxue; Ma Qingxue; et al. (Frigid Zone Medicine)
Small ubiquitin-like modifiers (SUMO)ylation is a dynamic and reversible post-translational modification playing pivotal roles in the regulation of cancer, diabetes, heart failure, and neurological diseases. However, whether SUMO inhibitors also have anti-hypertension effect remains yet to be explored.